(untitled) (Global Journals of Research in Engineering, 2024)
The main objective of this paper is to design Al-jubha intersection and the Roadways approaches optimized to better level of service Traffic design for this intersection include evaluation the current LOS for the intersection and design all possible solutions to reduce congestion delay and low level of service in this intersection This design will absolutely save time and money An intersection is a shared space that is used by more than one approach at a time A signalized intersection is one where the shared space is used alternatively by a fixed number of approaches for a predefined time interval as per the phasing scheme used for the intersection In this paper we made unconventional ideas to improve the intersection of the aljabaha signal the intersection is analyzed as an isolated intersection in this study using Synchro 8 and HCM 2010 standards The simulation results the median U-Turn and signal optimization improve the intersection level of service from E-B The delay for this intersection was reduced to 48 8 11 8